2020
DOI: 10.21203/rs.3.rs-29202/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and associated factors of undernutrition among pregnant women visiting ANC clinics in Silte zone, southern Ethiopia

Abstract: Background: Maternal undernutrition is highly prevalent in underdeveloped countries. Hence, this study was intended to determine the prevalence and associated factors of undernutrition among pregnant women visiting ANC follow up clinics of health facilities.Method: Facility-based cross-sectional study was conducted from July to January 2019. Systematic random sampling technique was used to select 422 study participants from 11 randomly selected health facilities. Data was collected by using a structured-inter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…This finding was in agreement with the reported result from a rural community in southern Ethiopia which was 41.2% [ 22 ]. The result of this study was higher than those studies conducted in other areas of Ethiopia, 31.8% in Central Refit Valley [ 15 ], 9.2% in Wondogenet District southern Ethiopia [ 16 ], 21.8% in Silte zone southern Ethiopia [ 17 ], 19.8% in Dessie town, northeastern Ethiopia [ 14 ], 19.5% in Eastern Ethiopia [ 13 ], 24% in humanitarian setting in Ethiopia [ 18 ], 16.2% in Gondar hospital [ 20 ] and 14% in Gondar town [ 21 ]. The discrepancy might be due to differences in socio-demographic characteristics, geographical variation, cultural beliefs such as food taboos, poor nutritional intervention programs in the Konso district.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…This finding was in agreement with the reported result from a rural community in southern Ethiopia which was 41.2% [ 22 ]. The result of this study was higher than those studies conducted in other areas of Ethiopia, 31.8% in Central Refit Valley [ 15 ], 9.2% in Wondogenet District southern Ethiopia [ 16 ], 21.8% in Silte zone southern Ethiopia [ 17 ], 19.8% in Dessie town, northeastern Ethiopia [ 14 ], 19.5% in Eastern Ethiopia [ 13 ], 24% in humanitarian setting in Ethiopia [ 18 ], 16.2% in Gondar hospital [ 20 ] and 14% in Gondar town [ 21 ]. The discrepancy might be due to differences in socio-demographic characteristics, geographical variation, cultural beliefs such as food taboos, poor nutritional intervention programs in the Konso district.…”
Section: Discussioncontrasting
confidence: 64%
“…In Ethiopia, the prevalence of undernutrition in pregnant women varies from 9.2-41.2%. It was reported in Central Refit Valley, Wondogenet District in Ethiopia, Silte zone, Southern Ethiopia, Dessie Northern Ethiopia, Eastern Ethiopia, Gondar town and hospital in Northern Ethiopia, humanitarian setting of Ethiopia, Shashemene, in a rural community in southern Ethiopia, 31.7, 9.2, 21.8, 19.8%, 19.5, 16.2, 14.4, 24, 34, 35.5, and 41.2%, respectively [13][14][15][16][17][18][19][20][21][22]. The most acceptable explanation for this wide variation is likely to be the fact that variation in the contextual factors of pregnant women's undernutrition.…”
Section: Introductionmentioning
confidence: 99%
“…The current study found that the prevalence of undernutrition in pregnant women was (13)(14)(15)(16)(17)(18)(19)(20). The discrepancy might be due to difference in sociodemographic characterstics, geographical variation, cultural belives such as food taboos, poor nutritional intervention program in Konso district.…”
Section: Discussionmentioning
confidence: 60%
“…In Ethiopia, the prevalence of under nutrition in pregnant women varies from 9.2%-34%. It was reported in Central Refit Valley of Ethiopia, Wondogenet District in Ethiopia, Silte zone, Southern Ethiopia, Dessie Northern Ethiopia, Eastern Ethiopia, Gondar town and hospital in Northern Ethiopia, humanitarian setting of Ethiopia, Shashemene, 31.7%, 9.2%, 21.8%, 19.8%, 19.5, 16.2% ,14.4%, 24%, 34% and 35.5 (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 97%